Artifacts and pitfalls in shoulder magnetic resonance imaging - Marconi,Gustavo Felix (2015)
Abstract Magnetic resonance imaging has revolutionized the diagnosis of shoulder lesions, in many cases becoming the method of choice. However, anatomical variations, artifacts and the particularity of the method may be a source of pitfalls, especially for less experienced radiologists. In order to avoid false-positive and false-negative results, the authors carried out a compilation of imaging findings that may simulate injury. It is the authors’ intention to provide a useful, consistent and comprehensive reference for both beginner residents and skilled radiologists who work with musculoskeletal magnetic resonance imaging, allowing for them to develop more precise reports and helping them to avoid making mistakes.